WHY IS IT BETTER AT HOME? SERVICE USERS' AND CAREGIVERS' PERCEPTION OF HOME CARE - Kênia Lara Silva; Yara Cardoso Silva; Érika Guimarães Lage; Patrícia Alves Paiva; Orlene Veloso Dias (Universidade Federal do Paraná, 2017)
The objective was to analyze service users' perspectives regarding the attendance of their needs by the Home Care Service. This is a qualitative study, with a descriptive and exploratory approach, undertaken between February 2014 and July 2015. A total of 15 service users and 15 caregivers participated, from the Home Care Service of eight municipalities in the Brazilian state of Minas Gerais. The results indicated that the profile of the population attended is mainly older adults. The reasons for admission are diverse, and relate to the chronic nature of the health conditions. The team seeks to undertake the activities taking into account the service users' natural and radical needs. Attendance in the home is presented as the best option due to the comfort of the home, the link with the family and with the team, and to the fact that this overcomes the barriers to accessing other points in the healthcare network. It is possible to understand that, in the service users' perspective, care provided in the home presents new relationships which broaden access, autonomy and quality of life for the service user.